{6,6 '-Dimethoxy-2,2 '-[ethane-1,2-diylbis-(nitrilomethylidyne)]diphenolato} (ethanol)-dioxouranium(VI) - Şenyüz, N.; Yüksektepe, Ç.; Bati, H.; Çalışkan, N.; Büyuk̈güngör, O. (Int Union Crystallography, 2006)
In the title compound, [UO2(C18H18N 2O4)(C2H6O)], the U atom has a distorted pentagonal-bipyramidal geometry with a tetradentate Schiff base and ethanol ligands in the equatorial plane and oxo atoms in the axial positions. Complex molecules are connected by O-H⋯O and C-H⋯O interactions, forming dimers in the crystal structure. © 2006 International Union of Crystallography All rights reserved.